Clinical and Microbial Etiology Characteristics in Pediatric Urinary Tract Infection - Jiandong Lu; Xiaozhu Liu; Yi Wei; Chengjun Yu; Jie Zhao; Ling Wang; Yang Hu; Guanghui Wei; Shengde Wu (Frontiers Media S.A., 2022)
BackgroundUrinary tract infection (UTI) is a common occurrence in children. UTI and urological malformations are intimately linked. However, whether urinary tract malformations affect the clinical features of pediatric UTI remains unclear. The purpose of this study was to characterize the clinical features and microbial etiology of UTI in children.MethodsWe retrospectively reviewed the records of 741 patients with UTI treated at the Chongqing Medical University Affiliated Children's Hospital between 2015 and 2020. Patients with and without urological malformations were compared using propensity score matching (PSM).ResultsEscherichia coli was the most common causative microorganism of UTI, accounting for 40.5% of infections. One hundred twenty-two patients (16.5%) had urological malformations. PSM identified 122 matched pairs of patients with or without urological malformations. The proportion of patients with UTI caused by atypical microorganisms was significantly higher in patients with urological malformations (P = 0.048). Children with urological malformations showed longer duration of intravenous antibiotic treatment (P = 0.010), higher cost of treatment (P < 0.001), and higher prevalence of recurrence (23.8 vs. 10.7%, P < 0.001), compared with the normal group.ConclusionChildren with urological malformations are more likely to develop UTI with atypical microorganisms. Appropriate imaging examination and urine culture are strongly recommended for the diagnosis and management of pediatric UTI.